Biomechanical, Physiological and Anthropometric Determinants of Backstroke Swimming Performance: A Systematic Review - José M. González-Ravé; Fernando González-Mohino; Francisco Hermosilla Perona; Victor Rodrigo-Carranza; Inmaculada Yustres; David B. Pyne (Sports Medicine - Open)
Abstract Background Backstroke swimming is one of the four competitive strokes contested at international swimming events, and the second-slowest stroke after breaststroke. Achieving success in competition depends on the intricate interplay of various factors, and for top-ranked athletes, subtle differences can be decisive in determining the race outcome. The aim of this study is to identify the main energetic, biomechanical, and physiological factors influencing elite backstroke swimming performance in 50, 100, and 200-m events. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to identify relevant studies. A literature search on 3 databases (PubMed, Scopus, Web of Science) was finalised on September 26, 2024. Results A total of 938 studies were identified, and finally 35 studies met the inclusion criteria. The swimmers (n = 507 participants, n = 188 women) were classified as Tier 3 (Highly Trained/National Level) or Tier 4 (International Level). Studies included exhibited a low risk of bias following the Hindle scale (11 ± 2 points). All the studies were observational. Reference values have been provided with normative blood lactate, kinematics, race pace, performance testing and anthropometric characteristics for comparison purposes in 50, 100, and 200-m events. Post-race blood lactate concentrations were lower in the 50 m compared to the 100 m and 200 m events. Differences were evident in stroke rate (SR) reference ranges between events (50 m, 100 m, 200 m), anthropometric profiles (swimmers’ height and hand, foot, and leg length), and pacing profiles (50 m: all-out trend; 100 m: positive profile; 200 m: parabolic approach or fast-track strategy). Conclusions There is a distinctive physiological and biomechanical pattern for distances from 50-m to 200-m in backstroke swimming. The data provide athletes and coaches with normative reference values for blood lactate, kinematics, race pace, and anthropometric measures.